Python for MATLAB development : extend MATLAB with 300,000+ modules from the Python package index - Danial, Albert (Apress, 2022)
Python for MATLAB Development shows you how to enhance MATLAB with Python solutions to a vast array of computational problems in science, engineering, optimization, statistics, finance, and simulation.